ANALISIS KESULITAN BELAJAR SISWA PADA MATERI VIRUS DI KELAS X MIPA SMA NEGERI 1 RANTAU SELATAN TAHUN PEMBELAJARAN 2017/2018 - Fatimah Dian Sari Harahap; M. Yusuf Nasution (Jurnal Pelita Pendidikan, 2018)
This study aims to determine the level of learning difficulties students on Virus material in terms of cognitive aspects, learning indicators and factors causing. The method used is the analysis of the causes of students' learning difficulties. The research design is descriptive quantitative. Population in research is all students of class X IPA SMA Negeri 1 Rantau Selatan, Kab. Labuhan Batu. The sample was taken in total sampling as many as 129 students. The research instruments are multiple choice test and questionnaire. The results showed: (1) the percentage of students' learning difficulties on each cognitive aspect of C1, C2, C3, C4, C5 and C6 and 43.05%, 48.15%, 49.36%, 50, 17%, 61.54%, 69.93%; (2) indicator to differentiate body structure of virus with other creature equal to 53,03%, (3) indicator to identify virus characteristic by 42,24%, (2) explain the way of virus reproduction 53,72%, (4) indicator explain the role of virus for life equal to 56,64%, and (5) indicator communicate how to avoid self from danger of virus like influenza, AIDS, bird flu etc 50, 7%; and (3) factors that, inhibiting students in studying viral plant matter are physical, psychological, parent, biology teacher, lesson, school environment. It was concluded that there were students' learning difficulties on virus material in class X MIPA SMA Negeri 1 Rantau Selatan Tahun Learning 2017/2018.Keywords: learning difficulties, cognitive aspects, and factors causing learning difficulties